Masuknya Islam di Maluku Tenggara dan Peran Masjid Al-Mukarromah Sebagai Basis Penyebarannya - Ali Fahrudin (Jurnal Lektur Keagamaan, 2016)
This article attempts to uncover the history of Islam in Southeast Maluku and the role of the mosque Al-Mukarromah, as the oldest mosque and the center institution in the spread of Islam in the region. This study uses a descriptive exploratory archaeological historical approach that is supported by historical data. The study suggests some the following points: 1) Before Majapahit conquered Muar Island (Kei islands) in Southeast Maluku, Islam has entered into Kei Besar Island in the year 1295 AD. It is characterized by the arrival of Sultan Isa children who come from Basrah and settled on the island of Luang (Nusa Tenggara Barat now); 2) the Al-Mukarromah Mosque was established in Kei Besar Island when Larat Matdoan, the King of Langgiar Fer in 1536 AD was in power and also as a center for the propagation of Islam in the Kei Islands; 3) The mosque is very influential in spreading Islam in Southeast Maluku. This is evidenced by the establishment of customary law of Larvul Ngabal, as a customary order that brought together the tribes of the Southeast Maluku, where the symbol of its approval must be cleansed in Masjid AlMukarromah. Keywords: Islam, Southeast Maluku, Mosque, Masjid Al-Mukar-romah, Langgiar, Larvul Ngabal. Artikel ini mencoba mengungkap sejarah masuknya Islam di Maluku Tenggara dan peran masjid Al-Mukarromah, sebagai masjid tertua dan pusat penyebaran Islam di wilayah tersebut. Penelitian ini menggunakan metode eksploratif deskriptif dengan pendekatan historis arkeologis yang didukung dengan data-data sejarah. Temuan penelitian ini berhasil mengungkap hal-hal sebagai berikut: 1) Sebelum Majapahit berhasil menaklukkan Pulau Muar (kepulauan Kei) Maluku Tenggara, Islam telah masuk ke Pulau Kei Besar pada tahun 1295 M. Hal ini ditandai dengan kedatangan anak-anak Sultan Isa yang berasal dari Basrah dan bermukim di Pulau Luang (NTB sekarang); 2) Masjid Al-Mukarromah didirikan di Pulau Kei Besar pada saat Larat Matdoan, Raja Langgiar Fer berkuasa pada tahun 1536 M dan juga sebagai pusat penyebaran Islam di Kepulauan Kei; 3) Masjid ini sangat berpengaruh dalam penyebaran Islam di Maluku Tenggara. Hal ini dibuktikan dengan penetapan Hukum adat Larvul Ngabal, sebagai tatanan adat yangmemersatukan suku-suku di MalukuTenggara, yang pusakasimbol pengesahannya harus disucikan di Masjid Al-Mukarromah. Kata kunci: Islam, Maluku Tenggara, Mosque, Masjid Al-Mukar-romah, Langgiar, Larvul Ngabal.